الضغوط المهنية واستراتيجيات التعايش لدى الأطباء - حسن بالشيخ, حنان; مصطفى مسعود, غادة (مجلة كلية الاداب, 2024)
This research work entitled is to highlight the professional pressures and coping strategies adopted in its diverse scopes among the category of doctors in Benghazi city, and to explore the gender, and age differences related. The sample consisted of (118) participants of both genders. It was noticeable clear, from the given results, that the level of “professional pressures” in this study decreased, except after the overload was a bit high. The most handled strategies by the respondents were: planful problem-solving seeking social support, accepting responsibility, positive reassessment, self-control, distancing, and found that there were no gender and age differences in both “professional pressures and coping strategies